Evolution of searching effort for resources: a missing piece of the puzzle in the ideal free distribution paradigm - Forsman, Jukka T.; Kivelä, Sami M. (Blackwell, 2021)
Animals commonly search for information about available resources to select a breeding or foraging site or a mate. Searching can be costly, which is why even random selection of resources may pay off. However, the evolution of searching effort in relation to key ecological factors and its ecological consequences remain insufficiently understood. We build a model to analyze the evolution of searching effort for resources in relation to key ecological factors; the cost of information acquisition, the cost of competition and the distribution of resource qualities. Evolutionarily stable searching effort decreased with increasing cost of information acquisition, eventually resulting in a random choice of resources. With a very low cost of information acquisition, evolutionarily stable searching effort increased with increasing proportion of low-quality resources in the available resource distribution, while the opposite was predicted with a higher cost of information acquisition. Cost of competition had only a negligible effect on the evolution of searching effort, except that increasing cost of competition increased investment in information acquisition when a resource distribution was biased towards high-quality resources. Informed resource selection (above-zero investment in information acquisition) resulted in skewed distribution of individuals across resources. Consequently, expected fitness became more similar across resources with decreasing cost of information acquisition and associated increase in searching effort, thus approaching the prediction of the classical ideal free distribution (IFD) model stating that individuals distribute themselves so that fitness is invariant across resources. However, we predict a positive correlation between fitness and resource quality with biologically more realistic parameter values, contradicting the IFD model. Costly information acquisition may, thus, explain why IFD is not always found in empirical studies. Generally, our results imply that avoidance of poor choices is more important for the evolution of information acquisition strategies than making the very best choices.
Keywords: ekologia; kilpailuetu; habitaatti; information (communication); ideal free distribution; ideal despotic distribution; resurssinvalinta; competition; evolutionary invasion analysis; habitat selection; mate choice